2021
DOI: 10.1021/acsami.1c02413
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate-Like CuO2@SiO2 Nanospheres as H2O2 Self-Supplying and Robust Oxygen Generators for Enhanced Antibacterial Activity

Abstract: Reactive oxygen species (ROS)-induced nanosystems represent one of the most essential, efficient, and encouraging nanobactericides for eliminating bacterial infection concerning the increasing resistance threats of existing antibiotics. Among them, Fenton-type metal peroxide nanoparticles are exciting nanomaterials with intriguing physiochemical properties, yet the study of this antimicrobial agent is still in its infancy. Herein, a robust pH-responsive Fenton nanosystem is constructed by the assembly of coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Multitudinous nanoscale germicides, such as noble metal (eg. Au, Ag, Pd, Ru, Pt) [4][5][6][7][8][9][10][11][12] nanoparticles (NPs), metallic oxide [13][14][15][16][17] (eg. ZnO, TiO 2 and CuO) NPs, and carbonaceous nanomaterials [18][19][20] have been exploited as antimicrobial alternatives, which exhibit high potency with broad spectrum antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Multitudinous nanoscale germicides, such as noble metal (eg. Au, Ag, Pd, Ru, Pt) [4][5][6][7][8][9][10][11][12] nanoparticles (NPs), metallic oxide [13][14][15][16][17] (eg. ZnO, TiO 2 and CuO) NPs, and carbonaceous nanomaterials [18][19][20] have been exploited as antimicrobial alternatives, which exhibit high potency with broad spectrum antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that copper peroxide (CuO 2 ) nanodots could specifically be triggered by the acidic environment of tumors and produce a great deal of Cu 2+ and H 2 O 2 , and at the same time, Cu 2+ can directly reduce GSH to promote CDT. [19][20][21] Glucose oxidase (GOx) can efficiently catalyze glucose into gluconic acid and H 2 O 2 by utilizing O 2 as an electron acceptor, thus cutting off the energy supply of cancer cells and inhibiting tumor growth. 22 The process is known as GOx-based starvation therapy and has attracted increasing interest in cancer treatment due to its inherent biosecurity.…”
Section: Introductionmentioning
confidence: 99%
“…45 The generated H 2 O 2 was further catalyzed by Cu + to generate • OH with high reactivity through a Fenton-like reaction, which in turn enhanced the generation of ROS in CDT. 19,21,46 Meanwhile, Cu 2+ was reduced to Cu + by GSH for CDT. 21 The in vitro experiments have confirmed the advantages of such a synergistic therapeutic effect through the integration of starvation therapy and CDT, which is expected to facilitate the development of multi-mode therapy in tumor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[2] To date, over 700,000 deaths annually worldwide is caused by antibiotic resistant infections. [3] In addition, bacterial colonies are also an urgent problem of environmental pollution. Bacteria have developed an inherent ability to evade much of the activity of traditional antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug‐resistant (MDR) bacteria are a global crisis that increases morbidity and mortality among those infected and negatively impacts clinical outcomes in a wide range of populations, including intensive care units or those receiving surgery, transplant or cancer treatment [2] . To date, over 700,000 deaths annually worldwide is caused by antibiotic resistant infections [3] . In addition, bacterial colonies are also an urgent problem of environmental pollution.…”
Section: Introductionmentioning
confidence: 99%